Political of Religion in Digital Era: Analysis of Jean Baudrillard’s Thoughts - Rifki, Lalu Rifki Rahman (JURNAL PENELITIAN KEISLAMAN, 2025)
The rapid development of digital technology has profoundly reshaped the socio-political landscape, including the domain of religion. This article examines the phenomenon of religious politicization in the digital age through the lens of Jean Baudrillard's theories, particularly simulacra and hyperreality. Employing a descriptive-analytical approach, the study explores how digital media serve not only as communication channels but also as mechanisms for producing and manipulating religious meanings for political purposes. These religious simulacra construct a hyperreal environment in which public perceptions of religion are shaped by artificial representations, often exploited by political actors to gain influence and legitimacy. The article concludes that religious politicization in the digital era constitutes a form of simulation with significant implications for how religion is interpreted and experienced in contemporary society.